Phage Types of multidrug resistant Salmonella species in a rural area of Maharashtra, India - Sabiha, ST; Nilekar, SL (Bangladesh Journal of Medical Science, 2012)
Objective: The aim of the present study is to know Phage typing and antimicrobial susceptibility pattern of Salmonella species. Methods: A total of 32 Salmonella species isolated from stool and blood specimen were included in the study. They were sent for phage typing to Lady Hardinge Medical College, New Delhi. Antimicrobial susceptibility was done by using Kirby Bauer disc diffusion method. Results: Majority of Salmonella typhi belongs to phage type E1 and biotype I. Decreased susceptibility of the isolate was observed to Ampicillin, Cotrimoxazole, Cephalexin and Gentamicin. Majority of the isolates were sensitive to Ciprofloxacin. Conclusion: Predominant phage type was E1. The antibiotic sensitivity pattern is changing and resistant cases are emerging due to inappropriate use of antibiotics. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9821 BJMS 2012; 11(1): 37-39